Differential Responses of Arctic Vegetation to Nutrient Enrichment by Plankton- and Fish-Eating Colonial Seabirds in Spitsbergen - Zwolicki, Adrian; Zmudczyńska-Skarbek, Katarzyna; Matuła, Jan; Wojtuń, Bronisław; Stempniewicz, Lech (Frontiers in Plant Science, 2016)
The role of seabirds as sea-land biovectors of nutrients is well documented. However, no studies have examined whether and how colonial seabirds that differ in diet may influence terrestrial vegetation. Therefore, the purpose of the study was to describe and compare plant communities located in the vicinity of the two most common types of seabird colonies in Arctic, occupied by piscivorous or planktivorous species. Within 46 plots arranged in four transects in the vicinity of plankivorous (little auk, Alle alle) and piscivorous colonies (mixed colony of Brunnich’s guillemot, Uria lomvia, and black-legged kittiwake, Rissa tridactyla) we measured the following: guano deposition, physical and chemical characteristics of soil, total nitrogen and its stable isotope signatures in soil and plants, ground vegetation cover of vascular plants and mosses, and the occurrence of lichens, algae and cyanobacteria. Using LINKTREE analysis, we distinguished five plant communities, which reflected declining influence along a birds fertilization gradient measured as guano deposition. SIMPROOF test revealed that these communities differed significantly in species composition, with the differences related to total soil nitrogen content and δ15N, distinctive levels of phosphates, potassium and nitrates, and physical soil properties, i.e. pH, conductivity and moisture. The communities were also clearly distinguished by distance from the bird colony. The two colony types promoted development of specific plant communities: the immediate vicinity of the plankivorous colony characterised by a Deschampsia alpina–Cerrastium arcticum community while under the piscivorous colony a Cochlearia groenlandica–Poa alpina community was present. Despite the similar size of the colonies and similar magnitude of guano input, differences between ornithogenic communities were connected mostly to phosphate content in the soil. Our results show that the guano input from seabirds which have different diets can affect High Arctic vegetation in specific and more complex ways than previously realized.